US UKIndia

Every Question Helps You Learn

Can you count how many times the number 6 appears in this quiz?

This Math quiz is called 'Equations with Added Variables' and it has been written by teachers to help you if you are studying the subject at middle school. Playing educational quizzes is a fabulous way to learn if you are in the 6th, 7th or 8th grade - aged 11 to 14.

It costs only \$12.50 per month to play this quiz and over 3,500 others that help you with your school work. You can subscribe on the page at Join Us

An example of an equation is X = Y. The letters “X” and “Y” are often referred to as “expressions” and are joined together using the equal “=” sign. The expression on both sides of the equal sign will have the same value. Sometimes an expression may contain a variable. Let’s look at the following equations.

1.
7X - 8 = 132
21
140
56
20
7X - 8 + 8 = 132 + 8
7X - 8 + 8 = 7X
132 + 8 = 140
7X = 140
140 ÷ 7 = 20
20 x 7 = 140
X = 20
2.
27X + 44 = 341
21
11
31
33
27X + 44 - 44 = 341 - 44
27X + 44 - 44 = 27X
341 - 44 = 297
27X = 297
297 ÷ 27 = 11
11 x 27 = 297
X = 11
3.
99X - 196 = 200
44
114
14
4
99X - 196 + 196 = 200 + 196
99X - 196 + 196 = 99X
200 + 196 = 396
99X = 396
396 ÷ 99 = 4
4 x 99 = 396
X = 4
4.
14X - 98 = 98
4
24
44
14
14X - 98 + 98 = 98 + 98
14X - 98 + 98 = 14X
98 + 98 = 196
14X = 196
196 ÷ 14 = 14
14 x 14 = 196
X = 14
5.
19X - 51 = 63
4
5
6
7
19X - 51 + 51 = 63 + 51
19X - 51 + 51 = 19X
63 + 51 = 114
19X = 114
114 ÷ 19 = 6
6 x 19 = 114
X = 6
6.
22X + 88 = 660
6
16
26
36
22X + 88 - 88 = 660 - 88
22X + 88 - 88 = 22X
660 - 88 = 572
22X = 572
572 ÷ 22 = 26
26 x 22 = 572
X = 26
7.
32X + 91 = 283
6
16
26
36
32X + 91 - 91 = 283 - 91
32X + 91 - 91 = 32X
283 - 91 = 192
32X = 192
192 ÷ 32 = 6
6 x 32 = 192
X = 6
8.
3X - 5 = 25
15
10
5
8
3X - 5 + 5 = 25 + 5
3X - 5 + 5 = 3X
25 + 5 = 30
3X = 30
30 ÷ 3 = 10
10 x 3 = 30
X = 10
9.
12X + 16 = 244
28
19
26
13
12X + 16 - 16 = 244 - 16
12X + 16 - 16 = 12X
244 - 16 = 228
12X = 228
228 ÷ 12 = 19
19 x 12 = 228
X = 19
10.
6X + 15 = 153
23
33
13
43
6X + 15 - 15 = 153 - 15
6X + 15 - 15 = 6X
153 - 15 = 138
6X = 138
138 ÷ 6 = 23
23 x 6 = 138
X = 23
Author:  Christine G. Broome